2022
DOI: 10.3389/fresc.2022.968314
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for enhancing social skills of individuals with intellectual disability: A systematic review

Abstract: Individuals with intellectual disability who suffer from comorbid mental health problems are likely to experience difficulties in socialising. Deficits in social skills are also associated with challenging behaviours and self-injury. This paper presents global evidence from a systematic review of literature on such issues as ‘interventions’; ‘social skills development’, and ‘individuals with intellectual disability’. A thorough search of various bibliographic databases identified 1 124 academic papers. Ten pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The social acceptance of students with SEN is lower than that of their typically developing peers; however, they show more negative and less positive social interactions (Schwab et al, 2014). For these reasons, it would be important to teach social skills to children with SEN (Jacob et al, 2022;Kavale & Forness, 1996), which https://doi.org/10.52291/ijse. 2023.38.32 Changes in the Social Characteristics of General Classroom Communities ... might help develop and maintain their relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The social acceptance of students with SEN is lower than that of their typically developing peers; however, they show more negative and less positive social interactions (Schwab et al, 2014). For these reasons, it would be important to teach social skills to children with SEN (Jacob et al, 2022;Kavale & Forness, 1996), which https://doi.org/10.52291/ijse. 2023.38.32 Changes in the Social Characteristics of General Classroom Communities ... might help develop and maintain their relationships.…”
Section: Discussionmentioning
confidence: 99%
“…These factors were considered to inhibit the effective adoption of social media by people with ID. Internet use can be complex for people with ID since they may have deficits in cognitive, social, and adaptive functioning (American Psychiatric Association, 2013;Jacob et al, 2022a;Tassé et al, 2016). A person's cognitive ability affects their ability to process words, which is an essential digital competency when using the Internet (Wu et al, 2014).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Frontiers Sports Act Living questioned whether physical activities may or may not affect people with intellectual disabilities; however, the primary outcome may change as the study progresses, as the sample size of the study was exiguous, as the authors also acknowledged [9]. A study conducted by the Journal of Intellectual Disability Research confirmed that adults with intellectual disabilities have low physical fitness levels.…”
Section: Literature Reviewmentioning
confidence: 99%